Definitions of successful ageing: a brief review of a multidimensional concept - Urtamo, Annele; Jyväkorpi, Satu K.; Strandberg, Timo E. (Acta Biomedica Atenei Parmensis, 2019)
Successful ageing has become an important concept to describe the quality of ageing. It is a multidimensional concept, and the main focus is how to expand functional years in a later life span. The concept has developed from a biomedical approach to a wider understanding of social and psychological adaptation processes in later life. However, a standard definition of successful ageing remains unclear and various operational definitions of concept have been used in various studies. In this review we will describe some definitions and operational indicators of successful ageing with a multidimensional approach.